21 Influence of fractional flow reserve measurement on treatment-decisions in patients with recent acute non-ST elevation myocardial infarction. (9th June 2011) - Carrick, D; Behan, M; Foo, F; Christie, J; Norrie, J; Oldroyd, K; Berry, C
Abstract : Introduction: Non-ST elevation acute myocardial infarction (NSTEMI) is the most common form of acute coronary syndrome and has a relatively poor prognosis. Visual interpretation of the coronary angiogram is the standard approach to guide treatment decisions in patients with recent acute NSTEMI. The aim of our study was to determine whether measurement of coronary pressure derived fractional flow reserve (FFR), compared to coronary angiography alone, might influence treatment decisions. Setting: The cardiac catheterisation laboratory in a regional heart centre in the UK. Definitions: The clinical indication for FFR measurement was the presence of an intermediate coronary stenosis (50%–75% of the reference vessel diameter) which resulted in diagnostic and treatment uncertainty. FFR measurement was used to provide functional information on lesion severity and an FFR <0.80 was taken to represent a flow-limiting stenosis. Methods: The study involved three accredited interventional cardiologists and a study coordinator. The cardiologists separately reviewed the coronary angiograms and together with the clinical history, made a decision for medical therapy, PCI, CABG/MDT, or deferred management. The FFR results were then disclosed and the initial management decision was reviewed in light of the FFR result and changed as appropriate. Results: Of 1621 acute NSTEMI patients (January 2009–March 2010) in our hospital, 100 (6.2%) had FFR recorded. The treatment decisions for each cardiologist were: medical therapy 7%, 10%, 1%; PCI 64%, 70%, 60%; CABG/MDT 13%, 12%, 15%; deferred management 16%, 8%, 24%). The proportion of patients allocated to each treatment group differed between the 2nd and 3rd Cardiologist (p=0.02). Following FFR disclosure, each cardiologist changed his/her treatment decision in 58%, 50% and 62% of patients (p<0.05). Of the new decisions made following FFR disclosure, the proportion of patients allocated to medical therapy increased by 26%, 19% and 29%, whereas the proportion of patients allocated to deferred management or multi-vessel PCI decreased by 16%, 8%, 24% and by 5%, 7% and 5%, respectively (all p<0.05). The number of patients in whom the treatment decisions made by each cardiologist independently conformed (and so represented a consensus in at least 2 of the 3 decisions) increased from 74% to 92% as a result of FFR disclosure (p<0.001). Conclusion: In our hospital about 1 in 20 NSTEMI had a coronary pressure wire study because of diagnostic uncertainty based on coronary angiography alone. In NSTEMI patients selected for FFR measurement, the FFR resulted in a change in management in at least half of the patients. FFR use increased the proportion of patients in whom treatment decisions conformed suggesting FFR use may also help to reduce the variation in treatment decisions using angiography alone. These results support further studies of the clinical utility and prognostic implications of FFR measurement in patients with NSTEMI.